Life cycle assessment in choosing alternatives for energy sector development (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2014)
Development of industrial activities have negative effect on natural resources and environment therefore, production systems must respect the principles of sustainable development by minimize natural resource consumption and pollutant emissions. Life cycle assessment (LCA) of a industrial activities is a technical tool, a method that allows evaluation of the socio-economic activities in relation with the environment, from birth to death. The aim of this paper is analysis of resource and energy consumption in Romania, using LCA, that can identify environmental and socio-economic aspects of analyzed sector, for taking effective measures, to ensure quality requirements, social, economic, protect environment and improving energy.